The challenges of the agricultural export sector. The case of asparagus. - Mathews, Juan Carlos (1994)
The new environment in which agroindustry activity operates in Peru, proves that comparative advantages alone are not enough to compete in the international market. The development of the asparagus industry in our country illustrates this situation and throws into relief the challenges to be faced to achieve stability and growth.